The role of nursing staff in the prevention of vaccine adverse reactions and complications - Pawłowski, Piotr; Pawłowska, Paulina; Jakubowska, Klaudia; Nalepa, Dorota; Chruściel, Paweł; Kościołek, Aneta; Pasieczny, Krystian (Journal of Education, Health and Sport, 2018)
Infectious diseases, resulting from infection by various microorganisms, are still a current problem of humanity. For decades, they had led to the death of one million people, which was put an end to by the development of vaccinology, leading to a diametrical change in the global epidemiological situation. An epochal event in this process was the invention of vaccinations that significantly reduced the incidence of infectious diseases and even contributed to the almost total eradication of some of them.Vaccine adverse reactions (VARs), despite the continuous development of vaccinology, still constitute a problem. As indicated in a number of studies, their etiology is mainly related to the action mechanism of the vaccine, mistakes in their vaccination technique, as well as systemic pathologies, coexistence of infectious diseases or systemic defects associated with the site of vaccine application. The role of the therapeutic team, consisting of a doctor and nurse employed at the vaccination point, is early detection of contraindications to the technique of vaccination, prevention, as well as initial diagnosis and treatment of VARs.The article presents the basic issues related to the subject of vaccination, with the emphasis on the role of nursing staff in their realization and prevention of vaccine adverse reactions. This should be the basis for intensifying dissemination of knowledge on vaccination, leading to reduction in the incidence of adverse vaccine reactions in patients.